Impact of gravitational forces on Red Blood Cell dynamics in biofluid suspension - Murali, Anirudh; Sarkar, Ram Rup (Life Sciences in Space Research, 2025)
The growing interest in space exploration and human spaceflight has highlighted the critical challenges posed by microgravity on human physiology. Among these, a significant issue is space anemia, which adversely affects Red Blood Cells (RBC) and alters its behavior. RBC depends on biofluids, for their systemic transport, a process that experiences disruption in the microgravity environment. This study aims to quantitatively address the puzzle of how red blood cells are influenced by gravity when they are suspended in bio-fluid. Dissipative Particle Dynamics (DPD) approach was used to model blood and the cell by applying gravity as an external force along the vertical axis and varied from 0g to 2g during parameter sweeps. Key metrics, including Elongation and Deformation indices, pitch angle, and normalized center of mass, were utilized to assess cellular behavior. Results revealed that gravity induces shape changes and spatial alignment in red blood cells. The Elongation Index and the normalized center of mass declined linearly with the applied gravity. Correlation analysis showed a strong correlation between applied gravity and the aforementioned variables. Additionally, forces acting on the cell, such as drag, shear stress, and solid forces, diminished as gravitational force increased. Further analysis indicates that increasing gravity affected the cell's velocity, resulting in prolonged proximity to vessel walls and intensified viscous interactions with surrounding fluid particles, thereby triggering morphological changes. This study provides crucial insights into the biophysical effects of gravity on the red blood cell and presents a significant step toward understanding cellular dynamics under altered gravitational conditions.
Keywords: Altered gravity; Computational modeling; Dissipative Particle dynamics; Fluid flow; Red Blood Cell